Factors That Affect The Aggressiveness of Taxes on Companies in The Basic And Chemical Industrial Sectors - Bidandari, Firda Tri (Asosiasi Dosen Akuntansi Indonesia, 2025)
Companies operating in the basic and chemical industries will be examined for their tax aggressiveness in this investigation. There are three aspects to consider: institutional ownership, executive salaries, and the quality of presidents and directors. For 2020–2023, 36 different companies have shares listed on the Indonesia Stock Exchange (IDX). This is known as purposeful sampling. Multiple linear regression tests are used as an analysis tool. The study found that tax aggression was positively influenced by the nature of presidents and directors, negatively influenced by executive salaries, and not affected by institutional ownership. According to the study, other related characteristics should be included, and the study population should be expanded